Apakah Nilai Tukar dan Leverage dapat Meningkatkan Profitabilitas? - Herman Sjahruddin; Nining Saniapon; Ahmad Anto; Ardiansyah Halim (CV. Ulil Albab Corp, 2024)
The study, conducted over four years from 2018 to 2021, examines the impact of exchange rates and leverage on the profitability of company’s in the automotive and spare parts industry listed on the Indonesia Stock Exchange (IDX). Exchange rate is measured in US dollars (USD), leverage is measured by debt to equity ratio, and profitability is measured by return on investment. The sample consisted of 12 automotive and spare parts industry companies with a total of 48 data items processed by E-views 12. The results show that the USD exchange rate has a small positive effect on return on assets with a t-count of 0,767577 < t-table 2,01290 and a significance value of 0,4467 > 0,05. Although the debt to equity ratio shows that the results have an insignificant negative effect on investment taking, the calculation results in a t-count of -1.874010 < t-table 2,01290 and a significant value is known, namely 0,0674>0,05. The results of this study reveal that an increase (decrease) in the rupiah exchange rate towards the US dollar can increase the issuer’s profit margin. On the other hand, increasing leverage can reduce the company’s earnings